ERECTA controls low light intensity-induced differential petiole growth independent of phytochrome B and cryptochrome 2 action in Arabidopsis thaliana - van Zanten, Martijn (Landes Bioscience, 2010)
Plants can respond quickly and profoundly to changes in their environment. Several species, including Arabidopsis thaliana, are capable of differential petiole growth driven upward leaf movement (hyponastic growth) to escape from detrimental environmental conditions. Recently, we demonstrated that the leucine-rich repeat receptor-like Ser/Thr kinase gene ERECTA, explains a major effect Quantitative Trait Locus (QTL) for ethylene-induced hyponastic growth in Arabidopsis. Here, we demonstrate that ERECTA controls the hyponastic growth response to low light intensity treatment in a genetic background dependent manner. Moreover, we show that ERECTA affects low light-induced hyponastic growth independent of Phytochrome B and Cryptochrome 2 signaling, despite that these photoreceptors are positive regulators of low light-induced hyponastic growth.